Characterization of the miRNA regulators of the human ovulatory cascade. Issue 1 (December 2018) - Yerushalmi, G.; Salmon-Divon, M.; Ophir, L.; Yung, Y.; Baum, M.; Coticchio, G.; Fadini, R.; Mignini-Renzini, M.; Dal Canto, M.; Machtinger, R.; Maman, E.; Hourvitz, A.
Abstract Ovarian follicular development and ovulation are complex and tightly regulated processes that involve regulation by microRNAs (miRNAs). We previously identified differentially expressed mRNAs between human cumulus granulosa cells (CGCs) from immature early antral follicles (germinal vesicle - GV) and mature preovulatory follicles (metaphase II - M2). In this study, we performed an integrated analysis of the transcriptome and miRNome in CGCs obtained from the GV cumulus-oocyte complex (COC) obtained from IVM and M2 COC obtained from IVF. A total of 43 differentially expressed miRNAs were identified. Using Ingenuity IPA analysis, we identified 7288 potential miRNA-regulated target genes. Two hundred thirty-four of these target genes were also found in our previously generated ovulatory gene library while exhibiting anti-correlated expression to the identified miRNAs. IPA pathway analysis suggested that miR-21 andFOXM1 cooperatively inhibitCDC25A, TOP2A andPRC1 . We identified a mechanism for the temporary inhibition ofVEGF during ovulation byTGFB1, miR-16-5p and miR-34a-5p. The linkage bioinformatics analysis between the libraries of the coding genes from our preliminary study with the newly generated library of regulatory miRNAs provides us a comprehensive, integrated overview of the miRNA-mRNA co-regulatory networks that may play a key role in controlling post-transcriptomic regulation of the ovulatory process.